Alpha-tocotrienol as a possible indicator for monitoring the presence of palm mid-fraction in dark chocolate - Farahany, Elham Moazami (2006)
The compositional variations of tocopherols and tocotrienols composition of the genuine CB and PMF were investigated to introduce a more reliable indicator in detecting as well as quantifying the PMF in CB. The results suggested that the α-tocotrienol data presented could be utilized for the detection of the PMF admixture to CB. Detection and of PMF admixture to CB in a chocolate model system was conducted using α-tocotrienol as an indicator. This study focused on mono-addition of PMF to CB. The PMF was added to CB at 1, 2, 3, 4, 5, 10, 15, 20 and 25% levels. HPLC was used to detect the presence of PMF admixture to CB. The results derived from the model system indicated that by increasing the PMF amount at 0 to 15% to CB resulted in an increase in the concentration of the α-tocotrienol significantly (P<0.05). However, the addition of PMF amount more than 15% did not have any effect on the α-tocotrienol concentration. A linear plot with a high correlation of 0.9967 was obtained with standard error (SE) of 1.527. The PMF amount in chocolate was at 1.4, 2.8, 4.2, 5.6, 5.9, 6.2, 6.4, 6.7 and 7% levels. There was a significant difference (P<0.05) between the detected concentrations of the α-tocotrienol when the amount of the PMF was increased from 1.4% to 5.6%. However, the addition of PMF amount at 5.6 to 6.4% level did not have any effect on α-tocotrienol concentration. The interesting results were obtained when the amount of the PMF was increased from 6.4 to 7% where a significant difference was observed. A linear plot (R2 = 0.9837) was obtained with SE of 1.986. A validation test was conducted to verify the equation obtained from the regression analysis. The high correlation obtained indicated a good accuracy, reflecting a close relationship between the predicted and actual values obtained by theoretical and experimental, respectively. From these studies the use of α-tocotrienol as a promising indicator for detection and quantification of PMF in chocolate was demonstrated. The results suggested that the amount of the added PMF in the CB in chocolate was predictable in the condition when smaller and more than 5% PMF was added. Therefore, it can be concluded that the identification of the foreign fat added was made possible because only one type of the foreign fat was added in this experiment scheme.